AUTOBIOGRAPHISM IN THE HISTORY OF THE TEXT OF M. A. BULGAKOV’S NOVEL “MASTER AND MARGARITA” (Proceedings of Southern Federal University. Philology, 2025)
ttps://doi.org/10.18522/1995-0640-2025-1-108-117One of the features of M. A. Bulgakov’s novel poetics “The Master and Margarita” is autobiographism. The autobiographical nature of Bulgakov’s novel “The Master and Margarita” was considered by such researchers as M. O. Chudakova, I. F. Belza, N. P. Utekhin, L. M. Yanovskaya, V. Ya. Lakshin, A. Z. Vulis, V. A. Chebotareva, I. N. Sukhikh. A. I. Solzhenitsyn’s litters made on the pages of Bulgakov’s novel have particular importance for its study. These litters are resulting from the writer's thoughts about the autobiographical image of the master. M. O. Chudakova formulated and substantiated the provision that autobiographism is one of the main features of the poetics of Bulgakov’s novel “The Master and Margarita” and the writer’s work as a whole. The article first attempted to demonstrate this feature of the novel poetics based on textual analysis of its drafts. The textual analysis of the entire revision system of the novel allows us to see that the novel was created on the basis of comprehension of one's own life and creative experience, as well as how autobiography manifested itself in the text of the work during Bulgakov’s work on the image of the master. The history of the text of the novel demonstrates that the event that had occurred in the life of Bulgakov could be reflected in the novel immediately or years later. In our work we rely on the system of editions of the novel that we have established and its main text, reflecting the last creative will of the author to the fullest extent. The draft texts are conveyed by dynamic transcription, which will make visible the process of writer’s work on the creation and allow us to see the formation of the author’s intention. Fragments of the text from the diaries of S. V. Hyatsintova are transmitted in the same way (introduced into scientific circulation for the first time).Key words: М.А. Bulgakov, “The Master and Margarita”, autobiographism, poetics of a novel, creative history, textual analysis